Det danske bidrag til NORDLEXIN - Holmboe, Henrik (LexicoNordica, 1999)
The Swedish project LEXIN has inspired other Nordic countries to develop the idea of a common nordic project called NORDLEXIN. This paper is about the Dani sh contribution to the project. The three languages Danish, Norwegian and Swedish are similar to such an extent, that you can take advantage of it in building word bases with the central vocabularies and other teaching material to the benefit of immigrants and ref ugees in the three countries. To accomplish such a project is not just a question of finding the right linguistic and pedagogical solutions. It also depends on political choices and political willingness to invest in a number of languages, which we normally consider marginal in a Nordic context.